The Learning Process of The Rapa'i Geleng Dance At Seulawet Arts Groups in UIN AR-RANIRY Banda Aceh - Umul Aiman; Uliyana Uliyana; Novysa Basri; Novita Hidayani; Rizki Rahmad; Vinny Aryesha; Aris Munandar (Catharsis, 2024)
Although dances are generally performed by women, the traditional Acehnese dance "rapa'igeleng" is instead performed by a group of men, emphasizing cooperation, togetherness, and solidarity. Uniquely, there is a traditional oral product in the form of poetry that is also presented as an accompaniment to the dance. By analyzing dance learning behavior, this research aims to explain the learning processes undertaken by the male dance group at the traditional dance studio Seulawet at UIN Ar-Raniry Banda Aceh. To gain a deep understanding, a qualitative method with participatory observation was used to examine the competence of the trainers, objectives, teaching materials, teaching methods, and assessments. Interviews and training program documents were also used for source and data triangulation. The study concluded that the process of learning the rapa'igeleng dance at the Seulaweut Art groups at UIN Ar-Raniry Banda Aceh revealed that the dance trainers did not have a bachelor of art background, but were seniors who already had dance experience and had achieved success both domestically and internationally. Dancers and musicians from Seulaweut Art Groups are among the students of UIN Ar-Raniry. Teaching materials include the scope of the rapa'i geleng dance, the movements of the rapa'i geleng dance, the poetry of the rapa'i geleng dance, and how to play the rapa'i musical instrument, Teaching methods are the lecture method, question and answer method, and demonstration method. The media used in learning include the Rapa'i musical instrument, documentation books about traditional Acehnese dances, Rapai Geleng dance videos and the trainer evaluates each lesson.